Reverse Mortgages Payment Based on Type of House in Kuala Lumpur: Comparing HECM and MPRM - Fadilah RAMLI, Suraya; M REDZWAN, Norkhairunnisa; Aisyah M HATTA, Farah; Bokhari S ANUAR, Mohd; Nadhirah ZULKIFLI, Nazatul (International Journal of Engineering and Technology, 2018)
A reverse mortgages is a type of home loan for homeowners to receive an amount of money against the value of the house in the form of fixed monthly payments or a line of credit. It enables the elderly homeowners to access their home equity and hold up payment into cash of loan until a certain condition apply whereby the loan amount will not exceed the home value over the life of the loan. This study aims to compare reverse mortgages payment between the Home Equity Conversion Mortgages (HECM) model by United State and Malaysian Proposed Reverse Mortgages (MPRM) loan structure on every type of house in Kuala Lumpur. Both loan structures have slight difference in the loan amount. From gender perspectives, it shows that male received higher amount of payment received compared to female. This situation happens because the difference in the life expectancy where one of the elements of reverse mortgages payment, whereby female are longer live than male due to mortality perils. Thus, between two models, the model that gives more payment towards Malaysia elderly is HECM rather than MPRM.Â Â